(3eMGSHI GdJKHjJGJ hab GdfXGe GdeMGSHj GdeGdj GdLRGFQj (B:s (3JeGQjf hMdhd (B/s - (3YLjdI, eMeO Hf eHQhcs; (3SYjOGfj, eMeO GdSYjOs ((3GdLRGFQ(B: s (3GdfTQ GdLGeYj GdLOjO(B, s, 2020)
(3JfGhd gPG GdcJGH ehVhY eMGSHI GdJKHjJGJ hab GdfXGe GdeMGSHj GdeGdj GdLRGFQj, MjK bOe ef NdGdg eONd YGe ddeMGSHI, heJWdHGJ eMGSHI GdJKHjJGJ (B((3GdCUhd GdKGHJI(B) (3GdJQJjHGJ hGdeYGdLI, HGdGVGaI Gdi eLehYI ef GdJeGQjf hMdhdgG eY GdJMdjd hGdGSJfJGLGJ(B. s
(3GdeQGLY U(B.157 (3GdeNJUQGJ U(B.163 (3bGFeI eYGjjQ GdeMGSHI GdOhdjI hGdeGdjI U(B.165 (3GdeUWdMGJ GdeMGSHjI U(B.169 (3GdeNWW GdhWfj GdeMGSHj GdeGdj GdLOjO U(B.181s
Keywords: (3GdfXGe GdeMGSHj GdeGdj (B- (3GdLRGFQs; (3GdeMGSHI GdJMdjdjIs